Spatial expression and regulation of rice high-affinity nitrate transporters by nitrogen and carbon status - Feng, Huimin (Journal of experimental botany, 2011)
The high affinity nitrate transport system (HATS) plays an important role in rice nitrogen acquisition because, even under flooded anaerobic cultivation when NH(4)(+) dominates, significant nitrification occurs on the root surface. In the rice genome, four NRT2 and two NAR2 genes encoding HATS components have been identified. One gene OsNRT2.3 was mRNA spliced into OsNRT2.3a and OsNRT2.3b and OsNAR2.1 interacts with OsNRT2.1/2.2 and OsNRT2.3a to provide nitrate uptake. Using promoter-GUS reporter plants and semi-quantitative RT-PCR analyses, it was observed that OsNAR2.1 was expressed mainly in the root epidermal cells, differently from the five OsNRT2 genes. OsNAR2.1, OsNRT2.1, OsNRT2.2, and OsNRT2.3a were up-regulated by nitrate and suppressed by NH(4)(+) and high root temperature (37 °C). Expression of all these genes was increased by light or external sugar supply. Root transcripts of OsNRT2.3b and OsNRT2.4 were much less abundant and not affected by temperature. Expression of OsNRT2.3b was insensitive to the form of N supply. Expression of OsNRT2.4 responded to changes in auxin supply unlike all the other NRT2 genes. A region from position -311 to -1, relative to the translation start site in the promoter region of OsNAR2.1, was found to contain the cis-element(s) necessary for the nitrate-, but not light- and sugar-dependent activation. However, it was difficult to define a conserved cis-element in the promoters of the nitrate-regulated OsNRT2/OsNAR2 genes. The results imply distinct physiological functions for each OsNRT2 transporter, and differential regulation pathways by N and C status